Sympathetic innervation of interscapular brown adipose tissue is not a predominant mediator of oxytocin-elicited reductions of body weight and adiposity in male diet-induced obese mice - Edwards, Melise M.; Nguyen, Ha K.; Dodson, Andrew D.; Herbertson, Adam J.; Wolden-Hanson, Tami; Wietecha, Tomasz A.; Honeycutt, Mackenzie K.; Slattery, Jared D.; O’Brien, Kevin D.; Graham, James L.; Havel, Peter J.; Mundinger, Thomas O.; et al. (Frontiers in Endocrinology, 2024)
Previous studies indicate that CNS administration of oxytocin (OT) reduces body weight in high fat diet-induced obese (DIO) rodents by reducing food intake and increasing energy expenditure (EE). We recently demonstrated that hindbrain (fourth ventricular [4V]) administration of OT elicits weight loss and elevates interscapular brown adipose tissue temperature (TIBAT, a surrogate measure of increased EE) in DIO mice. What remains unclear is whether OT-elicited weight loss requires increased sympathetic nervous system (SNS) outflow to IBAT. We hypothesized that OT-induced stimulation of SNS outflow to IBAT contributes to its ability to activate BAT and elicit weight loss in DIO mice. To test this hypothesis, we determined the effect of disrupting SNS activation of IBAT on the ability of 4V OT administration to increase TIBAT and elicit weight loss in DIO mice. We first determined whether bilateral surgical SNS denervation to IBAT was successful as noted by ≥ 60% reduction in IBAT norepinephrine (NE) content in DIO mice. NE content was selectively reduced in IBAT at 1-, 6- and 7-weeks post-denervation by 95.9±2.0, 77.4±12.7 and 93.6±4.6% (P<0.05), respectively and was unchanged in inguinal white adipose tissue, pancreas or liver. We subsequently measured the effects of acute 4V OT (1, 5 µg ≈ 0.99, 4.96 nmol) on TIBAT in DIO mice following sham or bilateral surgical SNS denervation to IBAT. We found that the high dose of 4V OT (5 µg ≈ 4.96 nmol) elevated TIBAT similarly in sham mice as in denervated mice. We subsequently measured the effects of chronic 4V OT (16 nmol/day over 29 days) or vehicle infusions on body weight, adiposity and food intake in DIO mice following sham or bilateral surgical denervation of IBAT. Chronic 4V OT reduced body weight by 5.7±2.23% and 6.6±1.4% in sham and denervated mice (P<0.05), respectively, and this effect was similar between groups (P=NS). OT produced corresponding reductions in whole body fat mass (P<0.05). Together, these findings support the hypothesis that sympathetic innervation of IBAT is not necessary for OT-elicited increases in BAT thermogenesis and reductions of body weight and adiposity in male DIO mice.